Feasibility of laparoscopic major hepatectomy for hepatic paragonimiasis: two case reports. Issue 38 (September 2016) - Liu, Fei; Zhang, Jingyi; Lei, Chuanfen; Wei, Yonggang; Li, Bo
Abstract: Background: Though accumulated evidence proved that laparoscopic major hepatectomy was technically feasible, it remains a challenging procedure and is limited to highly specialized centers. Paragonimiasis is one of the most important food-borne parasitic zoonoses caused by the trematode of the genus Paragonimus. Although hepatic paragonimiasis is rare, the previous studies had investigated hepatic paragonimiasis from different perspectives. However, the safety and feasibility of laparoscopic major hepatectomy for hepatic paragonimiasis have not yet been reported in the literature. Methods: We here present 2 cases of hepatic paragonimiasis at the deep parts of the liver with treatment by laparoscopic major hepatectomy. One case is a 32-year-old male patient who was admitted to the hospital due to upper abdominal discomfort without fever for 1 month. The clinical imaging revealed that there was a lesion about 5.9 × 3.7 cm in the boundary of right anterior lobe and right posterior lobe of the liver with rim enhancement and tract-like nonenhanced areas. The other one is a 62-year-old female patient who was referred to the hospital for 1 month of right upper abdominal pain and fever. The ultrasonography showed that there was a huge hypoechoic mass (about 10.8 × 6.3 cm) in middle lobe of the liver with tract-like nonenhanced areas. Both patients were from an endemic area of paragonimiasis and the proportion of eosinophil in the second case was increased. Results: The preoperative diagnosis of the first case was ambiguous and the hepatic paragonimiasis was considered for the second case. The first case underwent laparoscopic extended right posterior lobe hepatectomy and the other case underwent laparoscopic extended left hemihepatectomy. Both operations went very well and the operation times for the 2 cases were 275 minutes and 310 minutes, respectively. The 2 patients' postoperative recovery was smooth without major postoperative complications (such as, bleeding, bile leakage, and liver failure). Moreover, the 2 patients were discharged on the 6th day and 7th day after surgery, respectively. The postoperative histopathological examination manifested hepatic paragonimiasis in both patients. Conclusion: This study suggests that the laparoscopic approach may be safe and technically feasible for hepatic paragonimiasis.